2006
DOI: 10.4161/cc.5.18.3206
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Switch to Pseudohyphal Growth in S. Pombe

Abstract: Several genetic mutants of fission yeast (Schizosaccharomyces pombe) that form multiple septa and pseudohyphae (i.e., branching growth) have been isolated.(1-15) The current understanding of these mutants is that they lack the ability to separate the two sister cells after formation of the septum. Here it is shown that switching to multisepta and pseudohyphal growth can be induced in a reversible manner in wild-type S. pombe cells by changing the growth conditions, thus indicating an inherent cellular switch. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…The NO production of the RAW264.7 cells stimulated by H2P70 was significantly increased at 50, 200, and 500 μg/mL than that of H1P70, which indicated that ARTP mutagenesis enhanced the macrophage activation activity of polysaccharides with molecular weights between 10–100 kDa and the activity of polysaccharides may be relation to the molecular weight and structure of the sugar chain. Some reports showed that the high molar mass was thought to be favorable structural parameters for their immunological and anti-tumor activity [42,43,44,45]. In this study, the polysaccharide fraction with a molecular weight of 5000–20,000 kDa also showed higher immunological activity at the concentration from 50 to 500 μg/mL.…”
Section: Resultssupporting
confidence: 53%
“…The NO production of the RAW264.7 cells stimulated by H2P70 was significantly increased at 50, 200, and 500 μg/mL than that of H1P70, which indicated that ARTP mutagenesis enhanced the macrophage activation activity of polysaccharides with molecular weights between 10–100 kDa and the activity of polysaccharides may be relation to the molecular weight and structure of the sugar chain. Some reports showed that the high molar mass was thought to be favorable structural parameters for their immunological and anti-tumor activity [42,43,44,45]. In this study, the polysaccharide fraction with a molecular weight of 5000–20,000 kDa also showed higher immunological activity at the concentration from 50 to 500 μg/mL.…”
Section: Resultssupporting
confidence: 53%
“…However, based on the hyphal morphology of the cell‐separation mutants, it is tempting to surmise that dimorphic transitions could be evoked also in S. pombe by modulating the activity of regulators of the cell‐separation machinery. The recent demonstration that even S. pombe can form hyphae in response to certain external stimuli such as stress or starvation (Amoah‐Buahin et al , 2005; Borup, 2006; Mitsuzawa, 2006) lends weight to this idea. However, a careful examination of the filamentous morphology reveals two kinds of hyphal growth patterns: hyphae containing bipolarly growing cells and hyphae composed of unipolarly extending cells.…”
Section: Phylogenetic Aspects − Two Kinds Of Mycelial Growthmentioning
confidence: 99%
“…Addressing conditions other than vegetative growth, e.g. sporulation, pseudohyphal growth (71) or stationary phase, might thus reveal specific functions of Thp1. In addition, UDGs might act differentially in contexts where targeted genome and chromatin editing is required, such as somatic hypermutation, where targeted enzymatic deamination is coupled to error-prone BER (3, 72), or active DNA demethylation, where targeted DNA oxidation is linked to BER (9, 30).…”
Section: Discussionmentioning
confidence: 99%